Strategi Peningkatan Kinerja Pemasaran Kain Tenun Sutera Melalui Analisa Bauran Pemasaran dan Inovasi Produk di Tengah Masa Pandemi Covid-19 - Azlan Azhari (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2021)
This study was conducted to determine the effect of implementing marketing strategies and innovations carried out in an effort to improve the marketing performance of Sengkang silk weaving during the Covid-19 pandemic. This research was conducted from May to June 2021 using a quantitative research approach. The research method used is using primary data and secondary data obtained from observations, in-depth interviews, and distributing questionnaires to respondents totaling 100 people obtained from the calculation of Slovin's formulation. The samples of this research are the people who are included as customers of Sengkang silk woven fabrics. The results showed that the analysis of marketing strategies consisting of product, price, promotion and distribution as well as product innovation had a positive and significant effect on increasing marketing performance on sales of Sengkang silk weaving products. This shows that the better application of products, prices, promotions, and distribution as well as product innovations that are carried out will have an impact on increasing marketing performance on silk weaving sales obtained by the owners of the Sengkang silk weaving craft.